Metode Pembinaan Karakter Islami (Akhlak) dalam Pemikiran Ibnu Miskawaih dan Imam Al-Ghazali - Paisal Ipanda Ritonga; Salminawati; Siti Rodhiyah; Siti Nurzana (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This writing is motivated by philosophical thought that has developed from pre-Ancient Greek times (6th century) to contemporary times (20th century and beyond). The development of philosophical thought is divided into several periodizations, including: periods of western philosophy starting from ancient times, the Middle Ages, modern times and the present. With the Renaissance, the philosophy of freedom, independence and independence was reborn. The discoveries of modern science began to be pioneered during the Renaissance, because it was known as the era of rebirth of human freedom to think. The science that advanced during the Renaissance was astronomy. Some famous figures of this era include: Nicholas Copernicus, Johannes Keppler, and Galileo Galilei. In the development of philosophy and science during the modern renaissance era, many discoveries and scientific developments occurred. Starting from Issac Newton (1643-1727) and Leibniz (1646-1716) and continued by Joseph Black (1728-1799), Henry Cavendish (1731-1810) to John Dalton (1766-1844). This research uses a library study (Library Research). This research collects information and data using various kinds of materials in libraries such as documents, books, papers, articles and journals. With information obtained from various sources in the library, we can conclude how philosophy and science developed during the modern renaissance era